An overview of the National Plan for the Promotion of Solidarityand Cooperative Rural Economy (PANFLES) - Aldana Gutiérrez, Luis Gabriel; Páez Peñaloza, Davis (Cooperativismo & Desarrollo, 2025)
This article aims to highlight the significant contribution that the solidarity economy sector has made in the social and political spheres, particularly in relation to the armed conflict and the building of a stable and lasting peace in Colombia. This process began on November 24, 2016, with the peace agreement signed between the Colombian government and the Revolutionary Armed Forces of Colombia (FARC). As a result, the national government developed the National Plan for the Promotion of the Solidarity and Rural Cooperative Economy (PANFLES), with the objective of fulfilling the commitments outlined in the Final Peace Agreement for Ending the Conflict and Building a Stable and Durable Peace. This plan emphasizes the solidarity economy model as a practical and proven approach to addressing the root causes of the conflict, and it is an integral part of the national plans for comprehensive rural reform.